Diagnosing COPD and supporting smoking cessation in general practice: evidence–practice gaps. Issue 1 (15th January 2018) - Liang, Jenifer; Abramson, Michael J; Zwar, Nicholas A; Russell, Grant M; Holland, Anne E; Bonevski, Billie; Mahal, Ajay; Phillips, Kirsten; Eustace, Paula; Paul, Eldho; Wilson, Sally; George, Johnson
Abstract: Objectives: To review the accuracy of diagnoses of chronic obstructive pulmonary disease (COPD) in primary care in Australia, and to describe smokers' experiences with and preferences for smoking cessation. Design, setting and participants: Patients were invited to participate if they were at least 40 years old and had visited participating general practice clinics in Melbourne at least twice during the previous 12 months, reported being current or ex‐smokers with a smoking history of at least 10 pack‐years, or were being managed for COPD. Interviews based on a structured questionnaire and case finding (FEV1 /FEV6 measurement) were followed, when appropriate, by spirometry testing and assessment of health‐related quality of life, dyspnoea and symptoms. Results: 1050 patients attended baseline interviews (February 2015 – April 2017) at 41 practices. Of 245 participants managed for COPD, 130 (53.1%) met the spirometry‐based definition (post‐bronchodilator FEV1 /FVC < 0.7) or had a clinical correlation; in 37% of cases COPD was not confirmed, and no definitive result was obtained for 9.8% of patients. Case finding and subsequent spirometry testing identified 142 new COPD cases (17.6% of participants without prior diagnosis; 95% CI, 15.1–20.5%). 690 participants (65.7%) were current smokers, of whom 360 had attempted quitting during the previous 12 months; 286 (81.0% of those attempting to quit) reported difficulties during previous quit attempts. Nicotine replacement therapy (205, 57.4%) and varenicline (110, 30.8%) were the most frequently employed pharmacological treatments; side effects were common. Hypnotherapy was the most popular non‐pharmacological option (62 smokers, 17%); e‐cigarettes were tried by 38 (11%). 187 current smokers (27.6%) would consider using e‐cigarettes in future attempts to quit. Conclusions: COPD was both misdiagnosed and missed. Case finding and effective use of spirometry testing could improve diagnosis. Side effects of smoking cessation medications and difficulties during attempts to quit smoking are common. Health professionals should emphasise evidence‐based treatments, and closely monitor quitting difficulties and side effects of cessation aids. Trial registration: Australian New Zealand Clinical Trials Registry ACTRN12614001155684.